2018
DOI: 10.1021/acs.jpcc.8b09400
|View full text |Cite
|
Sign up to set email alerts
|

How Contact Layers Control Shunting Losses from Pinholes in Thin-Film Solar Cells

Abstract: An absorber layer that does not fully cover the substrate is a common issue for thin-film solar cells such as perovskites. However, models that describe the impact of pinholes on solar cell performance are scarce. Here, we demonstrate that certain combinations of contact layers suppress the negative impact of pinholes better than others. The absence of the absorber at a pinhole gives way to a direct electrical contact between the two semiconducting electron and hole transport layers. The key to understand how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 69 publications
(96 reference statements)
0
21
0
Order By: Relevance
“…As is known, pinholes on perovskite are shown to increase the shunting problem and decrease V oc . [ 46 ] Moreover, grain size and crystal structure of the perovskite film are other important parameters for achieving high‐performing devices, which are substantially affected by perovskite film formation. [ 47 ] The corresponding size distributions of perovskite grains, depicted in Figure 5c, display an average perovskite grain size of ≈213 ± 83 and ≈263 ± 83 nm for compact and bilayer NiO x films, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…As is known, pinholes on perovskite are shown to increase the shunting problem and decrease V oc . [ 46 ] Moreover, grain size and crystal structure of the perovskite film are other important parameters for achieving high‐performing devices, which are substantially affected by perovskite film formation. [ 47 ] The corresponding size distributions of perovskite grains, depicted in Figure 5c, display an average perovskite grain size of ≈213 ± 83 and ≈263 ± 83 nm for compact and bilayer NiO x films, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…J d at −2 V varies by nearly five orders of magnitude depending on the polymer. It has previously been shown that extrinsic shunt paths caused by substrate defects, dust particles, or localized fluctuations in material properties can result in local increases in leakage currents and thus random variations in J d amongst nominally identical devices . By using relatively thick semiconductor layers (≈280 nm) such effects are reduced, leading to J d variation (at −2 V) of less than a factor of 2 within device batches (Figure S3, Supporting Information).…”
Section: Jd R and Eqe Of Bhj Opds Measured At V = −2 V At Photon Enmentioning
confidence: 99%
“…It has previously been shown that extrinsic shunt paths caused by substrate defects, dust particles, or localized fluctuations in material properties can result in local increases in leakage currents and thus random variations in J d amongst nominally identical devices. [24,25] By using relatively thick semiconductor layers (≈280 nm) such effects are reduced, leading to J d variation (at −2 V) of less than a factor of 2 within device batches ( Figure S3, Supporting Information). Although extrinsic shunt paths cannot be completely ruled out in these OPDs, their existence cannot explain the five orders of magnitude difference in J d across five different donor:acceptor blends given the comparatively minor intra-batch variation.…”
mentioning
confidence: 99%
“…Moreover, decreasing the RMS improves the contact with the absorber material, which enhances the performance of planar solar cells. [ 23,28 ] Figure 1e shows the Raman spectra of the different ETM films. All spectra exhibit peaks in the range of 237–330 cm −1 , which are related to the FTO substrate.…”
Section: Resultsmentioning
confidence: 99%
“…[ 29,30 ] These Raman modes, characteristics of the ZnO crystal with wurtzite structure, agree well with the previous results obtained for ZnO thin films deposited by a sol–gel method. [ 23,28 ] The Raman spectrum of the TiO 2 film shows the E g mode corresponding to the anatase phase at 155 cm −1 . [ 9 ] For the ZnO/TiO 2 sample, the characteristic peaks of both wurtzite ZnO and anatase TiO 2 are present.…”
Section: Resultsmentioning
confidence: 99%